What, if anything, are colours relative to? - Hyman, J (Cambridge University Press, 2005)
Colours have been described as relative to observers, relative to the circumstances in which they are observed, relative to languages and even as relative to ‘the human perceptual standpoint’ or, less chauvinistically, ‘the perceptual point of view’. As this variety of relativisms suggests, the blanket claim that colours are relative and the blanket denial of this claim are equally unhelpful. We need to ask what, if anything, are colours relative to. This is the first question I shall address. The second is whether the relativity of colours, such as it is, implies that they are less real than shapes or intervals in time.